Asymptotic Solutions of Systems of Linear Degenerate Integro-Differential Equations - Zavizion, G. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We construct asymptotic solutions of a singularly perturbed system of integro-differential equations in which the matrix coefficient of the derivative is degenerate at a point.